Gravity Threshold and Dose Response Relationships: Health Benefits Using a Short Arm Human Centrifuge - Kourtidou-Papadeli, Chrysoula; Frantzidis, Christos A.; Gilou, Sotiria; Plomariti, Christina E.; Nday, Christiane M.; Karnaras, Dimitrios; Bakas, Lefteris; Bamidis, Panagiotis D.; Vernikos, Joan (Frontiers in Physiology, 2021)
Purpose: Increasing the level of gravity passively on a centrifuge, should be equal to or even more beneficial not only to astronauts living in a microgravity environment but also to patients confined to bed. Gravity Therapy (GT) may have beneficial effects on numerous conditions, such as immobility due to neuromuscular disorders, balance disorders, stroke, sports injuries, etc. However, the appropriate configuration for administering the Gz load remains to be determined. Methods: To address these issues, we studied graded G-loads from 0.5g to 2.0g in 24 young healthy, male and female participants, trained on a Short Arm Human Centrifuge (SAHC) combined with mild activity exercise within 40-59 % MHR, provided by an onboard bicycle ergometer. Hemodynamic parameters, as cardiac output (CO), stroke volume (SV), mean arterial pressure (MAP), systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) were analyzed, as well as blood gas analysis. A one-way repeated measures ANOVA and pairwise comparisons were conducted with a level of significance p<0.05. Results: Significant changes in heart rate variability (HRV) and its spectral components (Class, Fmax, VHF) were found in all g loads when compared to standing (p<0.001), except in 1.7g and 2.0g. There were significant changes in CO, CI, and CP (p<0.001), and in MAP (p=0.003) at different AG levels. Dose-response curves were determined based on statistically significant cardiovascular parameters, as well as the optimal G level for training. There was a statistically significant main effect of gender in CO (p=0.002) and cardiac power (CP) (p=0.016) and a statistically significant decrease in the HF biomarker, for females only, during the AG training compared to standing condition. Conclusion: The study’s novelty is the broad range of graded AG loads investigated and the outcome measures which shed light on how centrifugation affects cardiovascular biomarkers according to the AG intensity and the participants’ gender. Additionally, provides a methodological framework that enabled us to validate the centrifuge utility as a medical device and precisely propose personalized gravity therapy for treatment or rehabilitation of individuals confined to bed.